Prevalence and Quality of Informed Consent for Patients Undergoing Cosmetic Procedures: A Cross Sectional Study - Alsaidan, Mohammed Saud; Abuyassin, Aisha H.; Alammar, Hanin S.; Hussien, Ghaiath (Acta Bioethica, 2021)
Background: Failure of the physician to disclose potential risks and benefits associated with cosmetic procedures is one of the main causes of legal disputes over informed consent. The objective was to assess the prevalence and quality of the informed consent given by patients who undergone cosmetic procedures and its association with post-procedure adverse events. Methods: It was a cross-sectional, online, questionnaire-based study conducted during September and October 2020. Eligible adult male and female patients who were attending a governmental dermatology clinic at Al-Kharj city (Saudi Arabia) were invited to join the study. Results: A total of 246 patients were included in the study. Out of 246, 111 (45.1%) patients performed at least one cosmetic procedure before, and 89 (80.2%) of them signed an informed consent. 62 (69.7%) of them signed a consent before the procedure, 17 (19.1%) reported post-procedure adverse events, 16 (18.0%) reported dissatisfactions, and 27 (30.3%) reported either. None of the consent characteristics were significantly associated with higher prevalence of post-procedure adverse events or non-satisfactions. Conclusions: The prevalence and the quality of informed consent before cosmetic procedures are inadequate. Urgent corrections are required to protect the patient’s rights and to legally protect the treating physician.